Gen Z PEMAHAMAN GEN Z TERHADAP TINDAKAN CYBERBULLYING DI PLATFORM INSTAGRAM: Abstrak, pendahuluan, metode penelitian, hasil dan pembahasan, kesimpulan, daftar pustaka - pinalis, dallih (Jurnal Common, 2024)
The growing and widespread use of social media can increase acts of cyberbullying and cyber harassment, especially among young people, which actions often occur on the instagram platform. So the higher use of instagram among gen z, especially in Semarang City students, can have a negative impact on cyberbullying. This can be a serious problem because it will have an impact on the victim's mental health, including anxiety depression, anti-social behavior, and have a desire to commit suicide. The purpose of this study to see the level of understanding and influence of gen z, especially students of Semarang City on cyberbullying actions on the instagram platform. This study uses quantitative methods with purposive sampling data retrieval techniques. The population in the study is Semarang City students with a sample obtained as many as 110 respondents through an online Google form questionnaire. The main research result showed that the variable of understanding and gen z had a positive and significant effect on cyberbullying, while the variable of instagram had a negative effect on cyberbullying that occurred in the study of students of Semarang City.Abstract should be written in English. The abstract is written with Times New Roman font, size 10 pt, Italic and single spacing. Please translate the abstract of manuscript written in English into Indonesian. The abstract should summarize the content cover the aim, methods and technique, also the result in no more than 250 words.